2001
DOI: 10.1002/1097-0142(20010415)91:8<1525::aid-cncr1161>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Serum endostatin levels are elevated in patients with soft tissue sarcoma

Abstract: BACKGROUND Solid tumors are angiogenesis dependent, and elevated levels of proangiogenic cytokines have been reported in a variety of histologies. Endostatin is an antiangiogenic fragment of the basement membrane protein, collagen XVIII. Because antiangiogenic protein fragments may be generated by tumor‐derived proteases, the authors sought to determine whether circulating levels of endostatin were elevated in patients with localized soft tissue sarcoma. METHODS The authors analyzed preoperative serum levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
66
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 18 publications
1
66
0
Order By: Relevance
“…Another hypothesis to explain this 'paradox' is that elevated serum endostatin mostly reflects ongoing angiogenesis, as it is known that (i) matrix metalloprotease, which is activated during angiogenesis, can cleave collagen and modify its structure (Xu et al, 2001;Hangai et al, 2002), and (ii) collagen XVIII is mainly synthesised in the perivascular basement membrane of tumourassociated blood vessels (Muragaki et al, 1995;St Croix et al, 2000;Guenther et al, 2001). This can explain that large and aggressive tumours will generate more soluble endostatin than small ones (Feldman et al, 2001). Finally, it should be noted that the functional status of the soluble endostatin detected in this study has not been ascertained, similar to other studies using the same competitive EIA (Feldman et al, 2002;Bono et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis to explain this 'paradox' is that elevated serum endostatin mostly reflects ongoing angiogenesis, as it is known that (i) matrix metalloprotease, which is activated during angiogenesis, can cleave collagen and modify its structure (Xu et al, 2001;Hangai et al, 2002), and (ii) collagen XVIII is mainly synthesised in the perivascular basement membrane of tumourassociated blood vessels (Muragaki et al, 1995;St Croix et al, 2000;Guenther et al, 2001). This can explain that large and aggressive tumours will generate more soluble endostatin than small ones (Feldman et al, 2001). Finally, it should be noted that the functional status of the soluble endostatin detected in this study has not been ascertained, similar to other studies using the same competitive EIA (Feldman et al, 2002;Bono et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It may seem paradoxical because VEGF is known for its proangiogenesis function while endostatin is an angiogenesis inhibitor. However, cumulative evidences indicate that serum endostatin and VEGF level are concomitantly escalated in many types of cancer 15,[24][25][26][27][28] including HCC. 15 Assuming the serum endostatin levels reflected that in tissues, the correlation between tissue endostatin/ C18 and VEGF level in HCC samples seemed to be consistent with such an observation.…”
Section: Discussionmentioning
confidence: 99%
“…21 Five other studies have demonstrated that circulating VEGF levels are significantly elevated in patients with soft-tissue sarcoma. [22][23][24][25][26] Patients with GIST have higher serum VEGF levels than healthy controls. 27 Most studies have reported that elevated circulating VEGF levels correlate with higher tumor grade and increased local disease burden, but not with the presence of metastatic disease.…”
Section: Soft-tissue Sarcomamentioning
confidence: 99%
“…22,[24][25][26] Preoperative circulating VEGF levels did not have prognostic significance in the 2 studies evaluating this issue. 23,25 Another study followed serum VEGF levels after surgical or medical therapy for soft-tissue sarcoma and found that rising VEGF levels heralded recurrent or refractory disease. 24 Circulating angiopoietin-2 and basic fibroblast growth factor (bFGF) levels are also elevated in patients with soft-tissue sarcoma compared with healthy controls.…”
Section: Soft-tissue Sarcomamentioning
confidence: 99%